2022
DOI: 10.1021/acs.jafc.2c01978
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Acts Through NFE2L2 to Prevent Hypoxia-Induced Apoptosis in Porcine Granulosa Cells via Activating Antioxidant Defenses and Mitophagy

Abstract: In mammals, a vast majority of ovarian follicles undergo atresia, which is caused by granulosa cell (GC) apoptosis. GCs in follicles are exposed to low oxygen. Hypoxia triggers reactive oxygen species (ROS) generation, which leads to cell oxidative stress and apoptosis. Sulforaphane (SFN), a phytochemical isothiocyanate enriched in cruciferous vegetables, has exhibited a crucial role in mitigating oxidative stress. To explore the effect of SFN on porcine GC apoptosis in a hypoxic environment, we handled the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Apoptosis and shedding of GCs are important characteristics of ovarian follicular atresia. Our many previous research demonstrated hypoxia‐induced GC cycle arrest and apoptosis may also be a key trigger for the initiation of porcine antral follicular atresia 6–9,14,33 . Our own RNA‐seq data implied that DNA damage repair pathways were enriched in the downregulated biological process in porcine GCs with high levels of hypoxia 14 .…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Apoptosis and shedding of GCs are important characteristics of ovarian follicular atresia. Our many previous research demonstrated hypoxia‐induced GC cycle arrest and apoptosis may also be a key trigger for the initiation of porcine antral follicular atresia 6–9,14,33 . Our own RNA‐seq data implied that DNA damage repair pathways were enriched in the downregulated biological process in porcine GCs with high levels of hypoxia 14 .…”
Section: Discussionmentioning
confidence: 60%
“…Our many previous research demonstrated hypoxia-induced GC cycle arrest and apoptosis may also be a key trigger for the initiation of porcine antral follicular atresia. [6][7][8][9]14,33 Our own RNA-seq data implied that DNA damage repair pathways were enriched in the downregulated biological process in porcine GCs with high levels of hypoxia. 14 Single-stranded and double-stranded DNA damage and oxidized base damage (such as 8-oxoguanine and thymine glycol) are greatly exacerbated in cells under hypoxic conditions, which may be attributed to multiple mechanisms of mitochondrial ROS production in cells.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Under normal conditions, Nrf2 is ubiquitinated and degraded in the cytoplasm by binding to Keap1. However, under stress conditions, Nrf2 dissociates from Keap1 and translocates into the nucleus to bind to the antioxidant response element, which initiates transcription and expression of downstream genes, such as HO-1, NQO-1, SOD, and CAT, which contribute to resistance to oxidative stress [ 31 , 32 ]. In this experiment, we found that HO-1 and NQO-1, two critical antioxidant enzymes, were remarkably upregulated at the transcriptional level by supplementation with Cy, compared to those in the model group.…”
Section: Discussionmentioning
confidence: 99%